Impact of the Different Types of Le Fort I Maxillary Surgical Movement on Nasal Width Changes: A Photogrammetric Analysis. (February 2021) - Lin, Yi-Yu; Denadai, Rafael; Chou, Pang-Yun; Yao, Chuan-Fong; Chen, Ying-An; Wang, Po-Fang; Lin, Clement Cheng-Hui; Chen, Yu-Ray
Abstract : Background: Le Fort I maxillary movements affect nasal width, but nasal width changes with specific movement types have not been formally addressed to date. Objectives: The purpose of this study was to analyze and compare the changes in nasal width with different maxillary movements. Methods: A retrospective study was performed among consecutive patients who underwent bimaxillary orthognathic surgery (n = 138) and who were grouped based on the type of maxillary movement (ie, maxillary advancement with intrusion [MAI], maxillary advancement with extrusion [MAE], and maxillary setback with intrusion [MSI]). Preoperative and 12-month postoperative nasal widths were analyzed photogrammetrically by 2 blinded evaluators. Results: Maxillary advancement with intrusion and MAE presented a significantly ( P < 0.05) higher alar base widening than MSI did, with no significant ( P > 0.05) differences between MAI and MAE. Maxillary advancement movements (MAI and MAE) showed significantly ( P < 0.05) higher alar base widening than maxillary setback movement (MSI). However, no significant ( P > 0.05) difference was observed between maxillary intrusion (MAI and MSI) and maxillary extrusion (MAE) movements. Conclusions: This study shows that the nasal width varies distinctly depending on the type of Le Fort I maxillary surgical movement. Abstract : Supplemental digital content is available in the text.